The impact of diversification strategy, leverage, IOS on real earnings management / Dr. MF Christiningrum, Ak. CA. - -, Dr. MFChristiningrum Ak. CA. (UiTM Cawangan Johor, 2019)
This study examines the impact of diversification strategies, the level of use of debt (leverage) and the investment opportunity set (IOS) on the performance and earnings quality of diversified firms. Earnings quality is measured by real earnings management. Diversification level is measured by Herfindahl index and number of corporate segments. The diversification strategies in this study are divided into 2 groups, namely related and unrelated diversification. Samples of this study are120 multi-segment companies (1,320 firm years) listed in Indonesia Stock Exchange for an 11-year period from 2002 to 2012. The results of the study also find that multi-segment strategy affect positively real earnings transactions (via discretionary costs of production and abnormal operating cash flow). The option to perform transactions in real earnings management is significantly influenced by the increase in the number of segments and the level of debts as well as the use of investment opportunities set (IOS).